VISUALISASI TEKNIK KOLASE DALAM FOTOGRAFI EKSPRESI GURAT KARAT - Laras, Ketut Gura Arta (Seni Media Rekam ISI Surakarta, 2010)
The selection of photography work object was not always in the beautiful shape. The uniqueness of an object could become its own attraction and inspiration in creating the photography work. The expression of the composition and visualization in a work art became the characteristic of the artist himself. Gurat Karat was a concept of photography work art which explored the shape, texture and color of the rust of metal, especially in the rust of iron. We could explore the simple items in our surrounding which were not longer used and already broken. The iron which was rusted had its own uniqueness and attraction to observe. The change of the characteristic and the shape was v ery contrast. Before being rusted, the surface of the iron would be smooth, but after being rusted, the surface would be rough and the color would change. It was a result of rusting process of the iron itself. The phenomenon eventually stimulated the researcher to take the rust theme of the iron as an object in this photography work art creation. In arranging this photography work, the researcher used esthetic theory of Monroe Beardsley which listed three basic esthetic charac teristics as follow: unity, intensity and complexity. The visual work in 3D display created the image of space and dimension in this work. Colase technique was used in creating this work by combining 2D photography work and the object in the original item in the photography work itself, or using the construction which was suitable with the stuck object which was adjusted with the weight of that object. In a display, this work was not only enjoyed by the sense of sight but also the sense of touch since the texture in this work art could be touch.Keywords : Expressie Photography, Rust, and Collage